2016
DOI: 10.1371/journal.pone.0151529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature Downshift on the Transcriptomic Responses of Chinese Hamster Ovary Cells Using Recombinant Human Tissue Plasminogen Activator Production Culture

Abstract: Recombinant proteins are widely used as biopharmaceuticals, but their production by mammalian cell culture is expensive. Hence, improvement of bioprocess productivity is greatly needed. A temperature downshift (TDS) from 37°C to 28–34°C is an effective strategy to expand the productive life period of cells and increase their productivity (qp). Here, TDS in Chinese hamster ovary (CHO) cell cultures, initially grown at 37°C and switched to 30°C during the exponential growth phase, resulted in a 1.6-fold increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 114 publications
6
49
0
Order By: Relevance
“…We anticipated that some culture conditions could potentially alter impurity formation. In particular, culture temperature affects transcript levels in CHO cells (Bedoya‐Lopez et al, ; Gomez et al, ; Mason, Sweeney, Cain, Stephens, & Sharfstein, ; Oguchi, Saito, Tsukahara, & Tsumura, ; Yoon, Kim, & Lee, ) that could potentially mediate B‐Ab folding or correct chain assembly. We found culture temperature modulated two product‐related impurities in cell line X: half B‐Ab and high‐molecular‐weight (HMW) species.…”
Section: Introductionmentioning
confidence: 99%
“…We anticipated that some culture conditions could potentially alter impurity formation. In particular, culture temperature affects transcript levels in CHO cells (Bedoya‐Lopez et al, ; Gomez et al, ; Mason, Sweeney, Cain, Stephens, & Sharfstein, ; Oguchi, Saito, Tsukahara, & Tsumura, ; Yoon, Kim, & Lee, ) that could potentially mediate B‐Ab folding or correct chain assembly. We found culture temperature modulated two product‐related impurities in cell line X: half B‐Ab and high‐molecular‐weight (HMW) species.…”
Section: Introductionmentioning
confidence: 99%
“…Upon shifting the temperature at day 6, no significant difference in glucose utilization among the bioreactors was observed, and some of the bioreactors demonstrated low to no lactate accumulation. The low lactate accumulation may be due to the cells mimicking the stationary phase of the cell cycle as supported by recent studies, which have reported lactate consumption during the stationary phase in fed batch cultures (Bedoya-López et al 2016;Trummer et al 2006;Furukawa and Ohsuye 1998;Young 2013;Mulukutla et al 2012;Cruza et al 2000;Lao and Toth 1997).…”
Section: Discussionmentioning
confidence: 62%
“…In this manuscript, we describe the utilisation of RNASeq to characterise transcriptomics changes induced by temperature shift of a mAb producing CHOK1 cell line. For the initial phase of our analysis we sought, similar to other studies (Bedoya-López et al, 2016;Tossolini, López-Díaz, Kratje, & Prieto, 2018), to identify gene-level changes in expression following a decrease in cell culture temperature. Using a count-based differential expression method the abundance of > 1,300 genes were found to be significantly altered 24hrs after the temperature was reduced from 37°C to 31°C.…”
Section: Discussionmentioning
confidence: 99%